2020
DOI: 10.1007/s00335-020-09847-z
|View full text |Cite
|
Sign up to set email alerts
|

Baseline and innate immune response characterization of a Zfp30 knockout mouse strain

Abstract: Airway neutrophilia is correlated with disease severity in a number of chronic and acute pulmonary diseases, and dysregulation of neutrophil chemotaxis can lead to host tissue damage. The gene Zfp30 was previously identified as a candidate regulator of neutrophil recruitment to the lungs and secretion of CXCL1, a potent neutrophil chemokine, in a genome-wide mapping study using the Collaborative Cross. ZFP30 is a putative transcriptional repressor with a KRAB domain capable of inducing heterochromatin formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…However, the role of ZFP30 is largely unclear. Until recently, several of the few articles showed that ZFP30 is involved in regulating the innate immune response and the adipogenesis. ,, We have recently uncovered that the Zfp30 gene expression was significantly increased in the liver of NAFLD mouse models. However, whether ZFP30 directly regulates hepatic lipid homeostasis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of ZFP30 is largely unclear. Until recently, several of the few articles showed that ZFP30 is involved in regulating the innate immune response and the adipogenesis. ,, We have recently uncovered that the Zfp30 gene expression was significantly increased in the liver of NAFLD mouse models. However, whether ZFP30 directly regulates hepatic lipid homeostasis remains unknown.…”
Section: Introductionmentioning
confidence: 99%